Gerakan Hidup Bersih dan Sehat: Intervensi Sanitasi dan Edukasi Kesehatan di Desa Lero Kabupaten Donggala - Abdul Rivai; Dian Rahmayanti Rivai (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The Clean and Healthy Living Movement (CHLM) is an important initiative in improving public health, especially in rural areas such as Lero Village, Donggala Regency. This journal discusses sanitation interventions and health education implemented in the village. Using both qualitative and quantitative approaches, this study collected data on community awareness regarding sanitation and hygienic behavior. The results indicate that the intervention successfully improved knowledge and sanitation practices among the community, leading to a reduction in diseases related to poor sanitation.